1995
DOI: 10.1016/0009-2509(94)00494-c
|View full text |Cite
|
Sign up to set email alerts
|

Drying kinetics: A comparison of diffusion coefficients from moisture concentration profiles and drying curves

Abstract: Abstract--The mathematical formulation of mass transfer in drying processes is often based on the diffusion equation. In principle the diffusion coefficient as a function of moisture content has to be determined experimentally. The most direct approach is to derive the diffusion coefficient from experimental moisture concentration profiles in the material during drying. In this work, the diffusion coefficient determined in this way is called the actual diffusion coefficient. Very often, however, an indirect me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(22 citation statements)
references
References 6 publications
3
18
0
Order By: Relevance
“…In the fabrication of powdery chemicals like laundry detergents, molecular sieves, etc., this is a topic of continuing technical importance ( Fig. 58a and b) [595,[654][655][656]. So is process control with NMR sensors installed in the production line [61,127,131,447], which gains further momentum by the recent advances in the development of methods and hardware for mobile NMR.…”
Section: Discussionmentioning
confidence: 98%
“…In the fabrication of powdery chemicals like laundry detergents, molecular sieves, etc., this is a topic of continuing technical importance ( Fig. 58a and b) [595,[654][655][656]. So is process control with NMR sensors installed in the production line [61,127,131,447], which gains further momentum by the recent advances in the development of methods and hardware for mobile NMR.…”
Section: Discussionmentioning
confidence: 98%
“…It can also cause a loss of sealing properties of host rocks dedicated to nuclear waste storage once the underground cavities are excavated. Consequently, a large number of soils and rocks are also studied under drying conditions: kaolin clay (Ketelaars et al 1995), sandstone (Rousset-Tournier et al 2003), clayey formations (Musielak and Banaszak 2007;Cariou et al 2012) etc.…”
Section: Diversity Of Studied Materials Under Drying Conditionsmentioning
confidence: 99%
“…However, to further simplify the analysis, many authors have assumed high air flow rate over food product during drying so as to make the resistance of fluid to mass transfer at the air-food interface, negligible (Ketelaars et al 1995). Queiroz and Nebra (2001) analysed the experimental and theoretical results of drying kinetics of banana and concluded that incorporation of convective boundary condition in diffusion model is necessary for better simulation of experiments.…”
Section: Proposed Mathematical Modelmentioning
confidence: 99%